Service users' perceptions of recovery from recent-onset psychosis and their long journey to and through psychiatric treatment - Temesgen Worku Animaw; Chien Wai Tong; Li Yan; Välimäki Maritta Anneli; Bressington Daniel (WILEY, 2025)
A growing body of evidence highlights that individuals' understanding of mental illness and recovery influences their mental health care preferences. Journeys to psychiatric care settings vary across regions with different socio-economic and developmental characteristics. However, these journeys in low-income African countries have not been well explored. This descriptive qualitative study aimed to describe service users' journeys to and through psychiatric treatment and explore their conceptualizations of recovery from recent-onset psychosis. Nineteen adults with recent-onset psychosis were recruited from three hospitals in Ethiopia for an individual semi-structured interview. Data from in-depth face-to-face interviews were transcribed and thematically analysed. Participants' conceptualizations of recovery are summarized into four themes; "domination over the disturbance of psychosis", "complete medical treatment course and stay normal", "stay active in life with optimal functioning", and "reconcile with the new reality and rebuild hope and life". These perceptions of recovery were reflected in their accounts of the long and hurdled journey to and through conventional psychiatric care settings. Participants' perceptions of psychotic illness, treatment, and recovery seemed to result in delayed or limited care in conventional treatment settings. Misunderstandings about only requiring a limited period/course of treatment for a full and permanent recovery should be addressed. Clinicians should work alongside traditional beliefs about psychosis to maximize engagement and promote recovery. Integrating conventional psychiatric treatment with spiritual/traditional healing services may make an important contribution to early treatment initiation and improving engagement.